Austen and Autism: Reading Brain, Emotion and Gender Differences in Pride and Prejudice. - Dekel, Mikhal (Nineteenth Century Gender Studies)
A literary criticism of the book "Pride and Prejudice," by Jane Austen is presented. It explores the relationship between gender and classes, autonomy and women's growth, the pitfalls and victories of communication. It discusses the self-representation of the character of Mr. Darcy, and the benefits of the autistic mind which could be observed in the book's plot.